The cat who smelled a rat - Braun, Lilian Jackson (New York : Putnam, 2001)
Philanthropist James Qwilleran and his crime-solving cats investigate the murders of a volunteer fire-watcher and a local curling champ as a mysterious crime wave engulfs the town of Pickax.
Accelerated Reader AR
Keywords: Qwilleran, Jim (Fictitious character) -- Fiction; Journalists -- Fiction; Cats -- Fiction; Mystery fiction